Cultural Shock Experienced by Indonesian Students in Germany - Cindy Tenet Lay Grafia (Journal DaFIna - Journal Deutsch als Fremdsprache in Indonesien, 2021)
Culture shock involves a powerful, transformative process that takes place at both the individual and societal levels as important cultural forces are clashing. This article provides an account of the impact that culture shock has on individual identity and invites reflection on the social implications of culturally diverse encounters. A theoretical framework represented by the stages of culture shock developed by Paul Pedersen (2018) is described, and examples from the author’s personal and professional experiences are used as illustrations. In the effort to learn more about ourselves and the dynamic world in which we live, the author suggests that becoming more aware of and sensitive to the experience of culture shock can facilitate the development of expanded, more inclusive identities.